Lurasidone induces developmental toxicity and behavioral impairments in zebrafish embryos - Wentian Li; Fang Wang; Zhe Feng; Qianqian Cheng; Yuqing Huang; Lisheng Zhu; Han Xiao; Hongjian Gong (Frontiers in Psychiatry)
IntroductionLurasidone, a second-generation antipsychotic widely used for schizophrenia and bipolar disorder due to its favorable metabolic profile, has poorly understood potential developmental neurotoxicity. This study investigated its effects on zebrafish embryos to address this gap.MethodsZebrafish embryos were exposed to lurasidone at concentrations of 0, 0.4, 4, and 8 mg/L from 5 to 120 hours post-fertilization (hpf). We integrated morphological assessments, behavioral analyses, transcriptomic profiling, and neurotransmitter quantification to evaluate developmental neurotoxicity.ResultsLurasidone induced dose-dependent developmental toxicity, including reduced survival and hatching rates, decreased body length, and increased pericardial and yolk sac edema. Behavioral assessments revealed significant locomotor impairment and diminished touch response, especially at higher concentrations. Transcriptomic analysis identified 1,907 differentially expressed genes, with upregulation in circadian regulation pathways and downregulation in cell cycle and oxidative phosphorylation pathways. Neurotransmitter profiling showed significant reductions in glutamate, dopamine, and GABA levels.DiscussionThese findings demonstrate lurasidone’s potential to disrupt neurodevelopment, suggesting perturbations in excitatory/inhibitory neurotransmitter balance and critical cellular pathways. The results highlight neurodevelopmental risks during sensitive periods, underscoring the need for further safety assessment in vulnerable populations (e.g., pregnant women, young patients).